1953
DOI: 10.1042/bj0530374
|View full text |Cite
|
Sign up to set email alerts
|

The branched-chain fatty acids of mutton fat. 2. The isolation of (+)-12-methyltetradecanoic acid and of 13-methyltetradecanoic acid

Abstract: I953 a hydrolysate of the DNP derivative of fraction A, showing that the only glycine residues are Nterminal. The results with carboxypeptidase support the conclusion that asparagine is the C-terminal residue of the glycyl chain. In the case of acetylinsulin the liberation was approximately quantitative, assuming that it is present in both the glycyl chains, if one assumes that the molecular weight is 12 000. SUMMARY 1. Fraction A of oxidized insulin was hydrolysed with pepsin ancl chymotrypsin. The resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1953
1953
1971
1971

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Such a migration has been demonstrated by chemnical hydrogenation with a nickel catalyst (Sreenivasan et al 1963). The demonstration that this also occurs in the rumen might explain the presence of trans-octadec-16enoic acid in the depot fat of the sheep (Hansen, 1963), since such an acid was found to be present in the monoenoic acid fraction formed on hydrogenation.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Such a migration has been demonstrated by chemnical hydrogenation with a nickel catalyst (Sreenivasan et al 1963). The demonstration that this also occurs in the rumen might explain the presence of trans-octadec-16enoic acid in the depot fat of the sheep (Hansen, 1963), since such an acid was found to be present in the monoenoic acid fraction formed on hydrogenation.…”
Section: Discussionmentioning
confidence: 80%
“…The concentration of anteiso branched-chain C15 acid at various times after feeding suggested that it was metabolically formed from the foodstuffs, possibly from the isovaleric acid formed by amino acid deamination (Allison, Bryant, Keeney & Katz, 1961). This acid has been isolated from mutton fat by Hansen, Shorland & Cooke (1953).…”
Section: Resultsmentioning
confidence: 99%
“…Formic acid has not hitherto been reported as a constituent of natural fats, although it has been found in the venous and arterial blood of animals (Annison, 1954b). 180 acids with molecular weight lower than that of the C1l i8o acid 13-methyltetradecanoic acid (Hansen, Shorland & Cooke, 1953) have not formerly been isolated from animal depot fats, except isovaleric acid, which was identified in the body and head oils of dolphins and porpoises (Lovern, 1934). Until the present no antei8o acid with a molecular weight lower than that of 10-methyldodecanoic acid (Hansen, Shorland & Cooke, 1954a) had been shown to occur in animal depot fats.…”
mentioning
confidence: 99%
“…Typical RF values were as follows: phosphatidylethanolamine 0. 85 Although lecithin and plasmalogen frequently overlapped, as did also sphingomyelin and lysophosphatidylethanolamine, the individual con stituents were distinguishable by use of appropriate reagents. No appreciable separation according to degree of unsaturation or chain length of the fatty acids occurred.…”
Section: Co�iplex Lipidesmentioning
confidence: 99%
“…The branched-chain fatty acids of animal fats, so far as can be ascer tained, are saturated and appear to consist mainly of the odd-numbered (+) anteiso acids of which the Cl 3 (84), C l 5 (85,86,87), and C1 7 (88,89,90) members have been identified, and of even-and odd-numbered iso-acids of which the Cia (84), C14 (91), CIS (85,86,87), CIS (92), and C17 (88) members have been isolated. In addition, there have been isolated a CIS branched chain acid [which is probably 10-methylheptadecanoic acid (93)].…”
Section: Shorlandmentioning
confidence: 99%